The Impact of Meditation on The Improvement of Cognitive And Emotional Intelligence In Adolescents - Acep, Lauw; Damaradika, Tri Surya (Jurnal Mamangan, 2023)
Meditation, as a spiritual and mental practice, has become an increasingly popular global phenomenon in recent decades. This study aims to explore the impact of meditation on improving cognitive and emotional intelligence among adolescents at Dharma Sukha Vihara and Theravada Buddha Sasana Vihara. The research method employs a qualitative approach with a case study design, involving 15 adolescents aged 15–18 who have participated in a meditation program for at least two months. Data was collected through semi-structured interviews, participatory observation, and document analysis. The findings demonstrate that meditation positively improves concentration, cognitive awareness, emotional regulation, and problem-solving abilities. Participants reported enhanced focus in academic activities, better stress management, as well as increased empathy and social relationships. These results are supported by neuroscientific evidence indicating that meditation induces structural and functional changes in brain regions associated with attention, memory, and emotional regulation